IMPLEMENTASI TIME-DRIVEN ACTIVITY-BASED COSTING DAN STRATEGI HARGA PADA AGENSI PEMASARAN DIGITAL KREATIF - Bintang Nugroho; Nureni Wijayati (Jurnal Proaksi, 2023)
This research purposes to propose the application of Time-Driven Activity-Based Costing (TD ABC) with contribution margin analysis as a problem-solution for PT CRV, a creative digital marketing agency in Indonesia, which is having difficulties using the costing method to carry out cost-based pricing strategy. This research adopts explanatory sequential mixed methods, framed by an intensive case study with data triangulation. The actual cost of PT CRV is used to build TD ABC model and uses this model for contribution margin analysis. This research reveals that (1) TD ABC can be implemented in PT CRV and this cost-per-activity model can accommodate the increasingly complex and dynamic activities of making advertisements in digital media faced by 360-digital marketing agencies. (2) Contribution margin analysis can help management to improve their pricing through cost-based pricing strategy for every service offered by PT CRV.